Where we stand class matters - Hooks, Bell 1952-2021 (Routledge, 2000)
Drawing on both her roots in Kentucky and her adventures with Manhattan coop boards, bell hooks provides a successful black woman's reflection, personal, straightforward, and rigorously honest on how our dilemmas of class and race are intertwined, and how we can find ways to think beyond them." Quelle: teilweise Klappentext (back cover).
Keywords: Hooks, Bell -- 1952-2021; United States -- Race relations; Rassenverhoudingen; Sociale klassen; Social classes -- United States; Sexismus; Armut; Soziale Klasse; Arbeiterklasse; Rassenfrage; Schwarze Frau; Ausgrenzung; Kapitalismus; Rassismus; Soziale Situation; Klassengesellschaft; Wirtschaftliche Lage; USA; Autobiografie